FRI0223 Is performance of the 2015 acr/eular gout classification criteria affected by disease duration and gender? results from an italian multicentre study focused on the management of crystal-induced arthritides (ATTACK STUDY). (12th June 2018) - Ughi, N.; Zanetti, A.; Frallonardo, P.; Hoxha, A.; Lorenzin, M.; Ariani, A.; Ceccarelli, F.; Cimmino, M.A.; Scirocco, C.; Raffeiner, B.; Bortoluzzi, A.; Di Matteo, A.; et al.
Abstract : Background: Gout is a common form of arthritis, but early disease and phenotypes related to gender 1 may favour diagnosis misclassification, unless monosodium urate (MSU) crystals are searched for in synovial fluid (SF). The 2015 ACR/EULAR gout classification criteria 2 were validated in Rheumatology and primary settings, 3 and the impact of disease features on performance were observed, 4 yet little studied. Objectives: To assess the performance of the 2015 ACR/EULAR gout criteria in a cohort of crystal-induced arthritides stratified by disease duration and gender in a real-life setting in Italy. Methods: In/outpatients referring to Rheumatology Units for acute arthritis were enrolled into an ongoing multicentre cohort study designed for achieving improvement in the management of crystal-induced arthritis (ATTACk) by the Italian Society for Rheumatology. Gout was defined as MSU +SF (gold standard), irrespective of the clinical diagnosis, and the ACR/EULAR criteria were applied as full (all domains) and clinical-only set excluding imaging and SF analysis. To classify a patient as having clinical gout, the sufficient criterion (MSU +SF) was ignored and cutoff score ≥8 was used. Overall sensitivity and specificity were calculated. Disease duration (early if <2 years) was considered and gender effect explored. Results: Of 199 adult patients (65±12 years, 75% male, 96% Caucasian) recruited in 11 hospitals, complete SF analysis and ACR/EULAR score were obtained in 105 (53%). MSU+were 62/105 (59%), 47/62 (76%) were non-tophaceous and 25 (40%) early diseases. Calcium pyrophosphate (CPP) was the most prevalent crystal in non-MSU+. Details on performance (95% confidence intervals) are shown in table and on a receiver operating characteristic plot (figure 1). Overall good performance and high specificity of full and clinical-only sets were observed. In early disease criteria had high specificity, but low sensitivity, while performance was stable in longstanding gout. Specificity (clinical-only) and sensitivity were low when criteria were applied to males and females, respectively. Conclusions: The overall performance of the 2015 ACR/EULAR gout criteria was good, particularly for the purpose of enrolling into trials. The impact of disease duration was confirmed 4 and should be considered for misclassification issues as well as in clinical practice. Exploratory findings on gender effect seem relevant and deserve further studies. References: [1] Jansen Dirken-Heukensfeldt KJM, et al. 2010. [2] Neogi T, et al. 2015. [3] Janssens HJEM, et al. 2017. [4] Louthrenoo W, et al. 2017. Disclosure of Interest: N. Ughi: None declared, A. Zanetti: None declared, P. Frallonardo: None declared, A. Hoxha: None declared, M. Lorenzin: None declared, A. Ariani: None declared, F. Ceccarelli: None declared, M. A. Cimmino Grant/research support from: Menarini, Speakers bureau: Menarini, C. Scirocco: None declared, B. Raffeiner: None declared, A. Bortoluzzi: None declared, A. Di Matteo: None declared, F. Furini: None declared, M. Manara: None declared, F. Salaffi: None declared, G. Carrara: None declared, C. A. Scirè: None declared, R. Ramonda: None declared